Mediastinal lymphangioleiomyomatosis: a case report and literature review - Wang, Yike; Wang, Quanyong; Shi, Lin; Zhao, Lei; Dou, Yana; Hao, Fene (Frontiers in Oncology, 2025)
Lymphangioleiomyomatosis (LAM) is a rare disorder that primarily affects women of childbearing age. It is characterized by the abnormal growth of smooth muscle-like cells. While LAM typically occurs in the lungs, it can also be found in the retroperitoneum and pelvis. However, cases originating in the mediastinum are extremely rare. This report discusses an unusual case of mediastinal LAM in a male patient with no abnormal clinical symptoms. The patient, a 70-year-old man, the chest computed tomography (CT) scan revealed an irregular hypodense mass in the left side of the anterior superior mediastinum. Interestingly, the mass did not exhibit significant enhancement in the arterial phase. Instead, it showed striated enhancement in the central area during the venous phase, with no abnormalities observed in the marginal area. To further understand this condition, we conducted a comprehensive review of relevant literature, focusing on the imaging characteristics of mediastinal LAM and the pathogenesis and therapeutic prognosis of LAM. By sharing this information, we aim to enhance understanding and knowledge of this disease.